Definición, funcionamiento y estructuración de geocomplejos morfodinámicos en la Alta Ribagorza aragonesa - Chueca Cia, Javier (Geographicalia, 2017)
This work attempts to define the different geocomplexes identified inthe Aragonese Alta Ribagorza above timberline area. In our study, the organization of altitudinal belts has been stablished taking basically as reference geomorphological morphodynamic elements -distribution patterns and intensity of processes- trying to combine integrating proposals of geoecological and systemic kind. Besides, a concise systematization of general characteristics of functional processes existing in the work area is done, analysing the interrelationships developed among them and their vertical organization.